ORTHOSTATIC SUPPORT IN PARAPLEGIC AND AMPUTEE PATIENTS: A CONTROLLED TRIAL - Gisele Harumi Hotta; Débora Pinheiro Aguiar; Gabriella Coelho Vieira de Melo Alves; Liana Praça Oliveira; Marie Aquino Melo de Leopoldino; Jefferson Pacheco Amaral Fortes; Francisco Carlos de Mattos Brito Oliveira; Francisco Fleury Uchoa Santos Junior (Acta Ortopédica Brasileira, 2024)
ABSTRACT Introduction: Functional incapacity caused by physical alterations leads to significant limitations in daily activities and has a major impact on the return of people with disabilities to the social space and the workplace. This calls for an evaluation of the long-term influence of the use of a device specially developed for orthostatic posture on the physiological, biomechanical and functional parameters of amputees and spinal cord patients. Objective: The objective was evaluate the effect of postural support device use on function, pain, and biomechanical and cardiologic parameters in spinal cord injury and amputees patients compared to a control group. Methods: The orthostatic device was used by the participants for a period of ten consecutive days, for three cycles of 50 minutes each day, and a 15-day follow-up. Participants were positioned and stabilized using adjustable straps on the shoulders, trunk, and hips. The primary outcome was brief pain inventory. Fifteen participants were included the control group, 15 in the amputee group, and 15 in the spinal cord group. Results: Our results demonstrate that the use of the device allows the orthostatic position of amputees and spinal cord patients evaluated for ten days, leading to improved functionality and pain in the spinal cord and amputee groups compared to the control group. In addition, no changes were observed for secondary outcomes, indicating that the use of the device did not cause harm interference to patients. Conclusion: The long-term use of the orthostatic device is beneficial for improving functionality, reduce pain in amputees and spinal cord injury patients. Level of evidence II; Therapeutic Studies - Investigating the results of treatment.